Experience of illness with chronic singultus: a qualitative interview study - Zugaj, Marco; Busch, Claudia; Züger, Andrea; Keßler, Jens (Orphanet journal of rare diseases, 2025)
BACKGROUND: Chronic singultus lasting longer than one month is a rare disease. Due to its low prevalence, generating evidence about it is difficult. Patients with chronic diseases struggle with considerable restrictions in their quality of life. Chronic hiccups can lead to problems such as insomnia, anorexia, fatigue, exhaustion, weight loss, and depression. The aim of this study was to gain a better understanding of the quality of life of patients with chronic singultus and their experiences in contact with the healthcare system and with the general population. - METHODS: The data were collected using semi-structured interviews. The data analysis was carried out using qualitative structuring content analysis according to Kuckartz and Rädiker. Reliability was ensured by joint interprofessional evaluation of the interviews by experts, considering different perspectives. - RESULTS: Interviews from 20 patients with chronic singultus were analyzed. Analysis yielded 43 categories that could be assigned to five main topics. The disease burden of the patients was high. In addition to physical symptoms such as concomitant gastroenterological symptoms, shortness of breath, and fatigue, psychosocial consequences such as shame, social withdrawal, anxiety, depression, and even suicidality led to reduced quality of life. - CONCLUSIONS: Ignorance and helplessness among healthcare stakeholders in the case of chronic singultus could lead to a marginalization of the disease and patients. Referring patients to a center with the appropriate expertise can help to avoid underuse, overuse, or misuse of healthcare. Therefore, the awareness of the disease among stakeholders must raise.
Gesehen am 29.08.2025